The anterior scleral thickness in primary open-angle glaucoma with high myopia - Mu Li; Liwen Chen; Zhaoxia Luo; Xiaoqin Yan (Frontiers in Medicine, 2024)
PurposeThis study aimed to investigate and compare the anterior scleral thickness (AST) among high myopia (HM), primary open-angle glaucoma (POAG), and POAG with HM (HMPOAG) groups.MethodsThirty-two HM eyes, 30 POAG eyes, and 31 HMPOAG eyes were included. The Schlemm’s canal (SC) area, trabecular meshwork (TM) thickness, scleral spur (SS) length, and AST were measured using swept-source optical coherence tomography. AST was measured at 0 mm (AST0), 1 mm (AST1), 2 mm (AST2), and 3 mm (AST3) from SS.ResultsThe HMPOAG group had significantly thinner AST, SS length, and TM thickness than the HM and POAG groups (all p < 0.05). In addition, the SC area of the HMPOAG group was also significantly smaller than that of the HM group (p < 0.001).ConclusionThe HMPOAG group had the thinnest AST, shortest SS, thinnest TM, and smallest SC. The thinnest AST might contribute to the shortest SS, and further to the thinnest TM and smallest SC in the HMPOAG group. AST might be a novel clinical indicator in the prediction and evaluation of POAG.